Petrophysical and Geochemical Investigation-Based Methodology for Analysis of the Multilithology of the Permian Longtan Formation in Southeastern Sichuan Basin, SW China - Shengqi Zhang; Jun Liu; Li Li; Nadhem Kassabi; Essaieb Hamdi (Energies, 2024)
Against the backdrop of the national strategic goals of carbon peaking and carbon neutrality, the imperative for China’s low-carbon new energy transformation is evident. Emerging as an efficient and clean new energy source, the coal-based “three gases” (coalbed methane, tight sandstone gas, and shale gas) have gained prominence. Nevertheless, the current exploration of the coal-based “three gases” is limited to individual reservoirs, posing challenges to achieving overall extraction efficiency. The primary obstacle lies in the conspicuous disparities in gas content among different reservoirs, with the causes of such disparities remaining elusive. To address this issue, this study focused on the Permian Longtan Formation (coal, shale, and tight sandstone) in the southeastern Sichuan Basin. Through a comparative analysis of the mineral composition, organic geochemical features, and pore structure characteristics, this study aimed to delineate reservoir variations and establish a foundation for the simultaneous exploration and exploitation of the coal-based “three gases”. The research findings revealed that the differences in reservoir characteristics account for the variations in gas content among coal, shale, and tight sandstone. The mineral composition of the rock formations in the study area primarily consists of quartz, feldspar, clay minerals, pyrite, calcite, and dolomite. By comparison, the coal samples from the four major coal seams in the study area exhibited relatively large pore sizes, which are favorable for gas accumulation.